Towards a knowledge society: new identities in emerging india - Singharoy, Debal K. (Delhi, 2014)
This book depicts the emergence of knowledge society across rural and urban spaces and among cross sections of social collectivities in India. It analyses the new economic momentum and socio-cultural milieu as set in motion with the emergence of this society. The ensuing impact on the pre-existing facets of social identity and marginality, and the processes of construction of new social identities therein are studied. This book delineates both the hope and despair, as produced with the arrival of the knowledge society, and identifies the scope and conditions of alternative choice and liberation for the people within the emerging socio-economic order of this society. Rich in empirical data, this monograph will interest students, researchers, teachers, policy planners and social activists.
Keywords: Information society-India